God, being, pathos: Abraham Joshua Heschel's theological rejoinder to Heidegger - Herskowitz, D (Brill Academic Publishers, 2018)
Martin Heidegger’s philosophy has elicited many theological responses; some enthusiastic, others critical. In this essay I provide an organized and critical analysis of Abraham Joshua Heschel’s theological critique of and rejoinder to the thought of the German philosopher. By looking at Heschel’s 1965 Who is Man? as well as earlier and later texts, I demonstrate the way in which Heschel presents his biblical theology as an alternative to Heidegger’s philosophy.